FOSTERING SPEAKING PROFICIENCY THROUGH STORY COMPLETION IN LANGUAGE DEVELOPMENT UNIT CLASS - Hidayah Nor; Insan Aulia; Muhammad Arinal Rahman (Universitas Darussalam Gontor, 2024)
The purpose of this descriptive qualitative study was to investigate the application of the story completion technique to foster students’ speaking proficiency and to pinpoint the difficulties that arise when doing the activities. An English tutor from Antasari State Islamic University's Language Development Unit, group 31, who works with eighteen students of different majors selected based on the purposive random sampling technique, participated in the study. Semi-structured interviews and observations were used to gather the data then analyzed by using Miles and Huberman’s theory which consisted of data reduction, data display, and drawing the conclusion. The results provide a step-by-step procedure for applying the story completion technique, which includes determining the vocabulary and grammar that students have acquired, choosing an appropriate topic, evaluating students' fluency in the target language, a suitable story topic is chosen, the class is arranged in a circle, the story is started, and it ends after a few sentences. Students then take turns continuing the story, adding one to three sentences at a time. They are also free to add new characters, events, and descriptions to the story, and it continues until a logical conclusion or student intervention occurs. Apart from that, the study brought to light several obstacles, including choosing stories that students can relate to, handling big class sizes, handling time limits, addressing personal issues, as well as evaluating and giving feedback to students. The knowledge gathered from this study helps to clarify how the story completion technique is used to develop speaking skills and offers helpful suggestions to language teachers on how to deal with the difficulties encountered while applying this technique. All things considered; the study's findings have a great deal to offer language teachers throughout the globe in terms of practical advice on how to improve language acquisition using interactive storytelling techniques while resolving typical challenges that arise in bilingual settings.